(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Description of knowledge on prevention of surgical site infections (SSIs) among medical staff in Son Tay general hospital, 2021 and some related factors. Method: A cross-sectional study was conducted on 151 medical staff. Results: The rate of medical staff with fully knowledge of SSI prevention is 36.42%, in which the rate of doctors is 38.3% and of nurses is 35.58%. Age group ≥30 (OR=2.82; 95%CI: 1.12 – 7.13); Department of Surgery (OR=13.61; 95%CI: 5.14 – 35.98); working year ≥10 (OR=2.54; 95%CI: 1.26 – 5.11) and number of patients cared for/day <8 (OR=3.43; 95%CI: 1.26 – 9 ,34) are factors related to the knowledge of medical staff about regarding SSIs. Conclusion: The medical staff’s knowledge of surgical site infection prevention is suboptimal; relevant factors should be considered when conducting ongoing training in the prevention of surgical site infections in hospitals.